Pediatric Neuromyelitis Optica Spectrum Disorders: Three Case Reports and Review of Literature - Seyed Mohammad Baghbanian; Abdorreza Naser Moghadasi; Mohammad Mehdi Nasehi (Mazandaran University of Medical Sciences, 2020)
Introduction: Neuromyelitis Optica Spectrum Disorder (NMOSD) is a rare autoimmune inflammatory and astrocytopathic demyelinating disease of the Central Nervous System (CNS). In most patients, an autoantibody to the water channel protein aquaporin-4 (AQP4) would cause humoral inflammatory demyelination and axonal damage. The disease is characterized by clinical syndromes of the optic nerve, area postrema, spinal cord, diencephalon, or cerebrum; or MRI finding related to these regions. According to recent consensus diagnostic criteria, NMOSD is categorized as NMOSD with AQP4-Ab and NMOSD without AQP4-Ab. Early onset is defined as the disease presentation before 17 years. According to the pediatric NMOSD working group, most clinical, laboratory characteristics, and neuroimaging findings of this disease are the same as adult onset one, and the same criteria could be used for pediatric NMOSD. Differentiation of Neuromyelitis Optica (NMO) from MS and Acute Disseminated Encephalomyelitis (ADEM) is vital in choosing the appropriate therapy. It has also been reported that some MS therapies could aggravate NMO and lead to permanent disability. Case Presentation: Three patients under the age of 17 years presented in the neurology clinic, because of their recurrent optic neuritis and cervical myelopathy. AQP4-Ab was positive in two patients, and the other patient was seronegative for AQP4-Ab. According to the recent international consensus definition, all of the patients went under treatment with corticosteroid pulse therapy in acute relapses. Then two of them received azathioprine as a disease-modifying therapy, and the other patient went under rituximab because of a new relapse in spite of azathioprine therapy. Azathioprine and rituximab were safe, and all patients tolerated them well without any significant side effects. Conclusions: Pediatric NMOSD is a rare but life-threatening disease, which pediatricians and pediatric neurologists must be aware of its presentations and treatment.